THE EFFECT OF FINANCIAL LITERACY, MONEY ETHICS, AND TIME PREFERENCES ON FINANCIAL BEHAVIOR OF HIGH SCHOOL STUDENTS (SMA) IN BENGKULU CITY - Fitri Santi; Trisno Supriadi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2021)
This study examines the effect of financial literacy, money ethics and time preference on financial behavior with time preference as a moderating effect. Financial literacy used in this research is financial attitude and financial knowledge. This study used 395 samples. We collected data using an online questionnaire. Data were examined using partial least square (PLS) technique. The results showed that financial attitudes, financial knowledge and money ethics have a positive effect on financial behavior, but time preference has a negative effect on financial behavior. the results in the sample group of low financial knowledge, financial knowledge and time preference have no effect. But the sample group in the advanced knowledge, only has no significant effect on financial knowledge.. We also find the effect of moderation in time preference to weakens the effect of financial attitudes on financial behavior.Penelitian ini menguji pengaruh financial literacy, money ethics dan time preferences terhadap financial behavior dengan time preferences sebagai variabel moderasi. Financial literacy yang digunakan dalam penelitian ini adalah financial attitude dan financial knowledge. Penelitian ini menggunakan 395 sampel. Kami mengumpulkan data menggunakan kuesioner online. Data diperiksa dengan menggunakan teknik partial least square (PLS). Hasil penelitian menunjukkan bahwa financial attitude, financial knowledge dan money ethics berpengaruh positif terhadap financial behavior, tetapi time preference berpengaruh negatif terhadap financial behavior. Hasil pada kelompok sampel pengetahuan keuangan rendah, financial knowledge dan time preferences tidak memiliki pengaruh terhadap financial behavior. Namun kelompok sampel pada pengetahuan tinggi, hanya financial knowledge yang memiliki pengaruh terhadap financial behavior. Kami juga menemukan pengaruh moderasi time preferences untuk memperlemah pengaruh financial atttude terhadap financial behavior.